1995
DOI: 10.1111/j.1476-5381.1995.tb17221.x
|View full text |Cite
|
Sign up to set email alerts
|

Ketanserin‐sensitive depressant actions of 5‐HT receptor agonists in the neonatal rat spinal cord

Abstract: 1 The monosynaptic reflex (MSR), recorded in vitro from the neonatal rat spinal cord, was depressed by 5-hydroxytryptamine (5-HT), 5-carboxamidotryptamine (5-CT), methysergide and R( + )-8-hydroxy-2-(di-n-propylamino) tetralin (8-OH-DPAT), and also by the selective 5-HTlD agonists, sumatriptan and N-methyl-3-(1-methyl-1-piperidinyl)-1H-indole-5-ethane sulphonamide (GR 85548).2 Ketanserin (1 gM) and methiothepin (1 gM) reduced the duration of depressions elicited by 5-CT, but not those produced by 5-HT, sumatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 36 publications
0
13
1
Order By: Relevance
“…Ketanserin failed to overturn MSR inhibition by bath-applied 5-HT in several previous studies (Crick and Wallis, 1991;Elliott and Wallis, 1992;Manuel et al, 1995), but in our study, MRS inhibition in response to bath-applied 5-HT was also reversed by ketanserin. 5-HT1D-like receptors rather than 5-HT2A receptors have been proposed to mediate ketanserin-sensitive MSR inhibition (Manuel et al, 1995). Interestingly, pCA provoked a particularly long blockade of MSR in the presence of GR 127935 (a 5-HT1B/D receptor antagonist), which was reversed by ketanserin.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…Ketanserin failed to overturn MSR inhibition by bath-applied 5-HT in several previous studies (Crick and Wallis, 1991;Elliott and Wallis, 1992;Manuel et al, 1995), but in our study, MRS inhibition in response to bath-applied 5-HT was also reversed by ketanserin. 5-HT1D-like receptors rather than 5-HT2A receptors have been proposed to mediate ketanserin-sensitive MSR inhibition (Manuel et al, 1995). Interestingly, pCA provoked a particularly long blockade of MSR in the presence of GR 127935 (a 5-HT1B/D receptor antagonist), which was reversed by ketanserin.…”
Section: Discussioncontrasting
confidence: 73%
“…However, ketanserin failed to reverse MSR blockade by bath-applied 5-HT in previous reports (Crick and Wallis, 1991;Elliott and Wallis, 1992;Manuel et al, 1995).…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…However at the h5-HT 1D cloned receptors used in this study, where it has been reported that there is no or little receptor reserve , the same pattern of intrinsic activity is seen suggesting that the partial agonism produced by GR127935 may be re¯ected at native 5-HT 1D receptors. Partial agonism has been reported for GR127935 in the rat neonatal spinal cord thought to contain 5-HT 1D -like receptors (Manuel et al, 1995). To reiterate, the great advantage of SB-224289 over the existing 5-HT 1B receptor antagonists GR127935 and SB-216641 is that this compound exhibits no positive intrinsic activity even in recombinant systems with high receptor reserve.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Huang & Peroutka (1987) reported that at least 33% of the total 5-HT binding sites in the rat spinal cord are distinct from 5-HT 1A , 5-HT 1B or 5-HT 2C . Since like 5-HT 1A&B receptors, the 5-HT 1D , 5-HT 1E , and 5- HT 1F receptors are negatively coupled to adenylate cyclase (Barnes & Sharp, 1999), they are also likely to produce synaptic depression (see Manuel et al, 1995). Though not presently investigated, these receptors may also contribute to the widespread depressant action of 5-HT.…”
Section: Synaptic Depressionmentioning
confidence: 99%